2004
DOI: 10.1108/07363760410525669
|View full text |Cite
|
Sign up to set email alerts
|

Promoting brand benefits: the role of consumer psychographics and lifestyle

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 25 publications
(40 reference statements)
1
99
0
1
Order By: Relevance
“…As with the development of any new area, there is debate about the alternative ways concepts can be defined. Some authors focus just on the benefits of customer value (e.g., Orth et al, 2004;Sweeney and Soutar, 2001). Others adopt a cost-benefit view, which assesses value on the basis of a "get for give" view.…”
Section: The Customer Value-loyalty Processmentioning
confidence: 98%
“…As with the development of any new area, there is debate about the alternative ways concepts can be defined. Some authors focus just on the benefits of customer value (e.g., Orth et al, 2004;Sweeney and Soutar, 2001). Others adopt a cost-benefit view, which assesses value on the basis of a "get for give" view.…”
Section: The Customer Value-loyalty Processmentioning
confidence: 98%
“…A full exposition of all aspects of the BPM can be found in Foxall (1996 and Foxall, Oliveira-Castro, James and Schrezenmaier (2007). Orth et al (2004), discussing benefits-sought segmentation, suggested that products as well as brand names are capable of contributing to several types of benefit to the consumer. The major difference between product and brand consists in that a product is "something that offers a functional benefit" (which is akin to utilitarian reinforcement) while the brand is "a name, symbol, design or mark that enhances the value of a product beyond its functional value" (which is akin to informational reinforcement).…”
Section: The Behavioral Perspective Modelmentioning
confidence: 99%
“…Fast moving consumer goods may be used for a variety of different purposes and circumstances and consumer may demand a range of different variables from even the simplest product. This type of segmentation has been used to explore, amongst many others, consumers purchases of beer (Orth et al 2004), financial services (Chang and Chen 1995), cinema audiences (Cuadrado and Frasque 1999), on-line consumers (Wu 2001, Bhatnager, andChose 2004) and tourists (Sarigollu and Huang 2005). However, benefits that consumers seek from fast-moving consumer goods are comparatively under-researched (Orth et al 2004).…”
Section: Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated the applicability of segmentation to sectors such as banking (Alfansi and Sargeant 2000), tourism and travel (Gonzalez and Bello 2002;Magson and Dipple 2004), education (Cheung et al, 2010) and the marketing of location (Leisen 2001;. The retail sector has also been the subject of numerous segmentation studies that have focused upon specific markets (Kımıloğlu et al 2010;Moschis et al 2004); customer loyalty (Cuthbertson and Laine 2004;Ziliani and Bellini 2004); e-commerce (Rafiq and Fulford, 2005;Tractinsky and Lowengart 2003) and retail brands (Baltas 2003;Orth et al 2004;Trinh et al 2009). Indeed Hassan and Craft (2005) argue that as a concept, segmentation occupies a pivotal role in modern marketing management.…”
Section: Segmentation Theorymentioning
confidence: 99%